Drosophila melanogaster Meigen: I. Susceptibility to Endosulfan and biomonitoring of its residues in kale - R. de Almeida, Garcia (1999)
The susceptibility of flies Drosophila melanogaster to endosulfan and the use of this organism in biomonitoring residues of the insecticide in kale was evaluated. In the condition of the bioassay, residues-film bioassay in the Petri dish, endosulfan degraded depending on the temperature and alpha isomer degrades faster than beta isomer. Bioassays conducted with D. melanogaster showed that the toxicity of the insecticide increases with the temperature (25 to 35°C) and that the females are more susceptible to the insecticide. LCso values calculated as a function of temperature, varied from 4.2 to 11.7 ug/g bw for the males and 2.8 to 8.1 I-lg/g bw for the females. The formulated product Thiodan CE was applied on kale (Brassica oleracea varo acephala) and the residues 01'endosulfan were determined by bioassay. The determination limit by bioassay is in the order of 0.1 mg/kg and the method presented a reproducibility with a coefficient of variation of 10%. The validation of the bioassay by gas chromatography confirm the viability of the bioassay with D. melanogaster in monitoring the residues of endosulfan in kale.